2010
DOI: 10.1592/phco.30.7.639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enhanced External Counterpulsation on Canadian Cardiovascular Society Angina Class in Patients with Chronic Stable Angina: A Meta‐analysis

Abstract: The results of our meta-analysis call for further long-term studies to determine the place of EECP therapy in the management of chronic stable angina. Currently, EECP therapy should be considered for patients with stable angina who are refractory to or not suitable for invasive therapy and/or medical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 46 publications
0
16
0
3
Order By: Relevance
“…939 The EECP Consortium reported results in 2289 consecutive patients undergoing EECP therapy at 84 participating centers, including a subgroup of 175 patients from 7 centers who underwent radionuclide perfusion stress tests before and after therapy. 940 Treatment was associated with improved perfusion images and increased exercise duration.…”
Section: Enhanced External Counterpulsationmentioning
confidence: 99%
“…939 The EECP Consortium reported results in 2289 consecutive patients undergoing EECP therapy at 84 participating centers, including a subgroup of 175 patients from 7 centers who underwent radionuclide perfusion stress tests before and after therapy. 940 Treatment was associated with improved perfusion images and increased exercise duration.…”
Section: Enhanced External Counterpulsationmentioning
confidence: 99%
“…The largest of these was randomised trial which enrolled 139 patients and reported reduction of self-reported angina episodes by ~25% and increased time to development of 1-mm ST depression by ~15%, as well as enhanced quality of life 85. A meta-analysis subsequently suggested that EECP achieved an improvement in angina by at least one CCS class in 86% of patients with stable angina pectoris, though this analysis was not restricted to those patients with RA 86. This technology is in common clinical use in Europe and the USA, and it has recently received a Class IIa Level of Evidence B recommendation in guidelines 26.…”
Section: Main Textmentioning
confidence: 99%
“…There was, however, a high degree of heterogeneity among the studies, which lessens confidence in the results of the meta-analysis (Q statistic P ¼ .008). 52 The EECP Consortium reported results from 2289 consecutive patients undergoing EECP therapy at 84 participating centers, including a subgroup of 175 patients from 7 centers who underwent radionuclide perfusion stress tests before and after therapy. 53 Treatment was associated with improved perfusion images and increased exercise duration.…”
Section: Enhanced External Counterpulsationmentioning
confidence: 99%